A Novel Advantage of HGMS Ordered Matrices. (2000) - Iacob, Gh.; Rezlescu, N.
Abstract : A novel benefit of an ordered High Gradient Magnetic Separation (HGMS) matrix, made up of parallel ferromagnetic wires is presented. One shows that the magnetic force Fm depends on α, the angle between the wires of the matrix and the applied magnetic field H 0 . There is a relation between the tilting angles and magnetic susceptibilities of particles pulled out from the mixture. This relation proves a practical possibility of separating a mixture only by choosing adequate tilting angles; the method is named separation in angular steps. Finally one shows two applications based on this principle: a separator which extracts successively and another one which extracts concomitantly different magnetic fractions from a granular mixture.